Evaluation of Endogenous Metabolic Markers of Hepatic CYP3A Activity Using Metabolic Profiling and Midazolam Clearance - Shin, K-H; Choi, M. H.; Lim, K. S.; Yu, K-S; Jang, I-J; Cho, J-Y (WILEY, 2013)
This study aimed to evaluate endogenous metabolic markers of hepatic cytochrome P450 (CYP)3A activity in healthy subjects using a metabolomics approach. Twenty-four subjects received the following medication during the following three study periods: 1 mg of i.v. midazolam alone (control phase), 1 mg of i.v. midazolam after 4 days of pretreatment with 400 mg of ketoconazole once daily (CYP3A-inhibited phase), and 2.5 mg of i.v. midazolam after 10 days of pretreatment with 600 mg of rifampicin once daily (CYP3A-induced phase). During each study period, 24 h before and after the administration of midazolam, urine samples were collected at 12-h intervals for metabolomic analyses. We derived an equation to predict midazolam clearance (CL) based on several of these markers. We demonstrated that a combination of the concentrations and ratios of several endogenous metabolites and the CYP3A5*3 genotype is a reliable predictive marker of hepatic CYP3A activity as assessed by i.v. administration of midazolam.
Keywords: CYTOCHROME-P450 3A4; IN-VIVO; 4-BETA-HYDROXYCHOLESTEROL; HUMANS; INDUCTION; INHIBITION; 6-BETA-HYDROXYCORTISOL; PHARMACOKINETICS; IDENTIFICATION; EXPRESSION